A LOOK ON VIOLENCE: REFLECTING ABOUT THE SCHOOL - Cinara Dalla Costa Velasquez; Jorge Luiz da Cunha (Travessias, 2009)
Through this work we want to make some reflexive notes about violence and its relationship between the company and school. It is necessary, day after day, rethinking the educational practices that are built on the tension and the conflict that is generated by the different ways that violence manifests itself among the subjects of education and society.It is relevant to highlight that the society, which we live, is facing crises in their new social morphologies and the new social morphologies reach the school, their subjects and the relationships involved between them, especially the interpersonal relationships between the educators and the learners. To do so, rethink the school, violence and society in its midst became an alert to the reconstruction of possible ways for the humanization of the school and the society, of which we are all subject authors, opportunities that can attenuate conflicting practices, these opportunities show latent in the daily routine, disclosed at any time, by various media in our